The Effect of 4-Methylcatechol on Platelets in Familial Hypercholesterolemic Patients Treated with Lipid Apheresis and/or Proprotein Convertase Subtilisin Kexin 9 Monoclonal Antibodies - Konečný, Lukáš; Hrubša, Marcel; Karlíčková, Jana; Carazo, Alejandro; Javorská, Lenka; Matoušová, Kateřina; Krčmová, Lenka Kujovská; Šmahelová, Alena; Blaha, Vladimír; Bláha, Milan; Mladěnka, Přemysl (Nutrients, 2023)
Elevated low-density lipoprotein (LDL) cholesterol levels lead to atherosclerosis and platelet hyperaggregability, both of which are known culprits of arterial thrombosis. Normalization of LDL cholesterol in familial hypercholesterolemia (FH) is not an easy task and frequently requires specific treatment, such as regularly performed lipid apheresis and/or novel drugs such as proprotein convertase subtilisin kexin 9 monoclonal antibodies (PCSK9Ab). Moreover, a high resistance rate to the first-line antiplatelet drug acetylsalicylic acid (ASA) stimulated research of novel antiplatelet drugs. 4-methylcatechol (4-MC), a known metabolite of several dietary flavonoids, may be a suitable candidate. The aim of this study was to analyse the antiplatelet effect of 4-MC in FH patients and to compare its impact on two FH treatment modalities via whole-blood impedance aggregometry. When compared to age-matched, generally healthy controls, the antiplatelet effect of 4-MC against collagen-induced aggregation was higher in FH patients. Apheresis itself improved the effect of 4-MC on platelet aggregation and blood from patients treated with this procedure and pretreated with 4-MC had lower platelet aggregability when compared to those solely treated with PCKS9Ab. Although this study had some inherent limitations, e.g., a low number of patients and possible impact of administered drugs, it confirmed the suitability of 4-MC as a promising antiplatelet agent and also demonstrated the effect of 4-MC in patients with a genetic metabolic disease for the first time.
Keywords: Blood Component Removal; LDL-cholesterol; Cholesterol, LDL; Antibodies, Monoclonal; lidé; Hyperlipoproteinemia Type II; hyperlipoproteinemie typ II; lipid apheresis; Subtilisin; separace krevních složek; 4-methylcathechol; subtilisin; Proprotein Convertase 9; Proprotein Convertases; proproteinkonvertasa subtilisin/kexin typu 9; monoklonální protilátky; familial hypercholesterolemia; proproteinkonvertasy; platelet; Humans